A política linguística em discursos sobre a língua inglesa: relações de poder em propagandas de escolas de idiomas - Costa, Wyllamy Samuel da (Universidade Federal Rural do Semi-Árido, 2020)
The English language is notably the most widespread language of contemporary times. This is clear after the Second World War, when the United States became a world power. Consequently, the English language gains the status of lingua franca, given that the language reached several countries, behind cinema and the internet. In view of this, there are numerous speeches that affirm the need to learn the English language. Thus, the objective of this study is to analyze the way that this language is discursivized in advertisements for language franchises. Considering how linguistic policy relates to power relations in the production of discourses on the English language. For this, the study is anchored in the perspective of Michael Foucault (1995, 1996, 1998, 2008 ) with regard to discourse, statement, discursive formation, truth, knowledge and power. As well as, theories defended by authors in the area of linguistic policy, such as Calvet (2007), Rajagopalan (2003, 2005, 2011), Spolsky (2004, 2009), Siqueira (2015, 2018), amongst others. The analysis corpus consists of five advertisements from the CNA, CCAA and FISK schools, which are available on YouTube. Regarding the methodology, it is a qualitative analysis. The analyzes reveal that language schools circulate speeches that focus on relations of knowledge and power that refer to the most attractive and pleasurable teaching, reaffirming the idea of learning the language as something indispensable, above all, because the language promotes the status of success and power. Keywords: Discourse. English language. Linguistic Policy
Monografia
Keywords: Discurso. Língua Inglesa. Política Linguística.; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS INGLESA